Poverty Reduction in Nigeria in the Last Decade - World Bank (World Bank, Washington, DC, 2017)
The report consists of four chapters. Chapter one profiles the trends in growth, household consumption, and poverty rates at the national level between 2004 and 2013. Descriptive statistics of consumption and selected poverty indexes are presented and a profile of the characteristics of the poor is given. The chapter concludes with an analysis of nonmonetary indicators. Chapter two unpackages the national level data into subnational results (six zones) and shows the high and increasing divide of socioeconomic indicators. Chapter three uses descriptive and econometric technics to identify the drivers of this divide. Chapter four concludes and provides a road map for policy action to effectively address this divide.